Desert crush / Muhd Ridzuan Mohd Zaini … [et.al.]. - Mohd Zaini, Muhd Ridzuan; Abdul Aziz, Ahmad Syahmi; Mohd Yunus, Mohd Syahmi; Anwar, Annazirul Zaffrullah; Abang Azahari, Abang Nurazam; Awg Shariee, Awg Mohd Shazani (2014)
Dessert Crush is our company name.The business is in the form of partnership which consist 6 members. Each partner contributes certain amount of capital as agreed in our agreement.Our main business activity is to provide variety type of dessert to eat.Our business will be operating at Jalan Mcdougall 93000 Kuching Sarawak. It will be commence in the beginning 1st January 2015.All partners are entitled to participate in the business management. We all agreed that Muhd Ridzuan Bin Mohd Zaini is our General Manager Ahmad Syahmi Bin Abdul Aziz is our Administration Manager, Mohammad Syahmi Bin Mohd Yunus and Annazirul Zafrullah Bin Anwar is our Marketing Manager, Abang Nurazam Bin Abang Azahari is our Operating Manager, Awang Shazani is our Financial Manager.